Burying the Past: Making Peace and Doing Justice after Civil Conflict by Nigel Biggar, ed. (Washington, DC: Georgetown University Press, 2001. 312 pages.) (American Journal of Islam and Society, 2003)
How should societies that have transitioned from authoritarian to democraticrule deal with the atrocities and gross human rights violations of theirimmediate past? Should those implicated in the crimes of past regimes beprosecuted? This sophisticated volume attempts to address such questions.About one-third of the book is comprised of well-reasoned theoreticalchapters that answer the above questions by creating a space in liberal justicefor forgiveness. The remainder consists of empirical contributions thatdescribe the ways in which international institutions and five countries(Chile, Guatemala, South Africa, Rwanda, and Northern Ireland) haveresponded to such crimes. Unlike the theoretical section, most contributionshere argue that while memory and forgiveness (the truth commissions) areimportant, they are not enough to meet the victims’ psychological needsand do not guarantee non-repetition. The introduction rightly acknowledgesthat some of the chapters argue in different directions.Doing justice in the aftermath of civil conflict is a thorny problem. In liberalism,criminal justice always has been straightforward: the courts, themouthpiece of objective law, have to mediate and impose punishment if theperpetrator is proven guilty. Punishment must consist of penalties that annulthe advantages seized by the criminal, compensate the victim in the case of ...